Applying the Semiotic Reading Model of Michael Riffaterre in the Interpretation of Mahmoud Darwish’s Poem - Hafsoh, Indah Sofi; Sa'dudin, Ihsan; Dzul'iman, Maman; Tarya, Tarya (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2024)
Mahmoud Darwish, a Palestinian poet, is a great example of this. He used his words to resist Israeli colonialism and was even hailed as a revolutionary poet for his anti-Israel stance. To interpret the reading of Mahmoud Darwish's “الجميلات هن الجميلات” and “كمقهى صغير هو الحب” poem under the theme of “هي” in “كزهر اللوز أو ابعد” collection. For this study, the qualitative descriptive method was employed. The researcher gathered primary and secondary data by reading and comprehending them carefully. The data was then identified, recorded, and categorized into groups, then analyzed using Michael Riffaterre's theory to address the research questions. Finally, the results of the analysis were used to conclude. The results of this research are the beauty of a woman is something universal, and every woman has a unique beauty that resembles and is present in every second line of every verse. And about love, which is like a small cafe, it’s true about the author of the poem. This research has two main benefits. Firstly, theoretically, it is expected to increase interest in the Arabic language and culture in Indonesia through the study of Arabic poem. Additionally, it aims to expand scientific knowledge related to the Arabic language and literature. Secondly, practically, this research is anticipated to contribute to the development of further research in the study of the Arabic language and literature. It can be used as a reference for solving various problems and as a consideration in future studies.